Development and Use of a Monoclonal Antibody Specific for the Candida albicans Cell-Surface Protein Hwp1 - Oh, Soon-Hwan; Martin-Yken, Hélène; Coleman, David A.; Dague, Etienne; Hoyer, Lois L. (Frontiers in Cellular and Infection Microbiology, 2022)
The Candida albicans cell-surface protein Hwp1 functions in adhesion to the host and in biofilm formation. A peptide from the Gln-Pro-rich adhesive domain of Hwp1 was used to raise monoclonal antibody (MAb) 2-E8. MAb 2-E8 specificity for Hwp1 was demonstrated using a hwp1/hwp1 C. albicans isolate and strains that expressed at least one HWP1 allele. Immunofluorescence and atomic force microscopy experiments using MAb 2-E8 confirmed C. albicans germ-tube-specific detection of the Hwp1 protein. MAb 2-E8 also immunolabeled the tips of some C. dubliniensis germ tubes grown under conditions that maximized HWP1 expression. The phylogeny of HWP1 and closely related genes suggested that the Gln-Pro-rich adhesive domain was unique to C. albicans and C. dubliniensis focusing the utility of MAb 2-E8 on these species. This new reagent can be used to address unanswered questions about Hwp1 and its interactions with other proteins in the context of C. albicans biology and pathogenesis.